Plastic Waste Reduction Campaign at the Traditional Market of Nyanggelan Village, Panjer, Denpasar - SAPUTRA, Komang Adi Kurniawan; Ekajayanti, L.G.P. Sri; SURIANI, Ni Nyoman (PT Batara Swastika Harati, 2024)
This article raises the theme of the plastic waste reduction campaign in the traditional market of Nyanggelan Village, Panjer, Denpasar. The increasing problem of plastic waste is a severe environmental challenge, especially in areas with high trading activity such as traditional markets. Through a participatory approach, this campaign aims to increase public and trader awareness of the negative impacts of plastic waste and the importance of good waste management. Activities include socialization, counseling, and training on using environmentally friendly materials as an alternative to plastic. In addition, this campaign also involves collaboration with the government and local organizations to create sustainable solutions. The results of this activity show an increase in public understanding of the importance of reducing plastic use and changes in behavior in choosing more environmentally friendly packaging. Through this effort, Nyanggelan Village can be an example for other areas in reducing the negative impacts of plastic waste and encouraging further action in maintaining cleanliness and environmental sustainability.